2012
DOI: 10.1007/s00535-012-0709-6
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescent imaging for detecting extrahepatic metastasis of hepatocellular carcinoma

Abstract: Extrahepatic metastases from HCC exhibited ICG fluorescence when illuminated by near-infrared light, indicating their capability to transport ICG. This imaging can be a useful tool for intraoperative detection of metastasis in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 12 publications
0
99
0
1
Order By: Relevance
“…2) Satou et al reported that ICG fluorescence could also be observed at extrahepatic metastases. 3) They reported that they had succeeded in identifying one pulmonary metastases out of two lesions that were explored using an ICG-NIF system; however, they reported that the excitation light was unable to reach another three lesions through a thoracotomy because their system was not an endoscopic device. In the present study, we used an endoscopic ICG-NIF system, which is able to access the entire thoracic cavity, and clear blue fluorescence was observed at the metastatic site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Satou et al reported that ICG fluorescence could also be observed at extrahepatic metastases. 3) They reported that they had succeeded in identifying one pulmonary metastases out of two lesions that were explored using an ICG-NIF system; however, they reported that the excitation light was unable to reach another three lesions through a thoracotomy because their system was not an endoscopic device. In the present study, we used an endoscopic ICG-NIF system, which is able to access the entire thoracic cavity, and clear blue fluorescence was observed at the metastatic site.…”
Section: Discussionmentioning
confidence: 99%
“…ICG fluorescence is detectable when a target lesion exists within 1 cm from the organ surface, 10,11) and small metastatic lesions of HCC with a diameter of 3 mm were reported detectable by an ICG-NIF system when the lesions were close to the pleural surface. 1,3) Therefore, the ICG-NIF system may be useful in identifying small metastatic lesions without the need of preoperative marking and exploration of small lesions unidentified by preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norihiro Kokudo (Department of Surgery, University of Tokyo, Japan) spoke about advanced liver resection using indocyanine green (ICG) fluorescence [10].…”
Section: Hepatobiliary Surgerymentioning
confidence: 99%
“…It would result in good functioning of organs or tissues. However, no such ideal method has been devised yet, although there are scattered reports of the use of various kinds of fluorescence dyes towards achieving this purpose [1][2][3][4][5]. The present review paper introduces one such ideal agent that could aid surgeons in realizing their dream: acridine orange (AO).…”
Section: Introductionmentioning
confidence: 99%